Efeito do disseleneto de difenila sobre alterações comportamentais e bioquímicas induzidas por anfetamina em camundongos - Figueira, Fernanda Hernandes (2012)
Selenium is an element that can modulate the dopaminergic neurotransmission. Studies show that diphenyl diselenide, an organic compound of selenium, has antioxidant activity improves depressive-like behavior and reduce the activity of the enzyme monoamine oxidase (MAO). However, there are few studies concerning about possible alterations of diphenyl diselenide in dopaminergic system. Thus, the purpose of the present study was to evaluate the effects of acute and sub-chronic treatment of diphenyl diselenide on amphetamine-induced behavioral and biochemical alterations in mice. In the acute treatment, the mice were treated with diphenyl diselenide (5 and 10 mg/kg, s.c.) or vehicle (10% Tween 80, s.c.) 30 min before administration of amphetamine (1.25 mg/kg, i.p.). After 25 min, locomotor activity was assessed with an open field and, also, the time of stereotypy and immobility was assessed in a glass cage. Sub-chronic treatment was conducted with seven administrations of diphenyl diselenide (5 and 10 mg/kg, s.c.), or its vehicle being one administration per day. On the eighth day, amphetamine (1.25 mg/kg, i.p.) was administered and the behavioral tests were conducted after 25 min. In both treatments ex vivo tests were performed: isoform activity MAO-A and MAO-B, and measurement of total protein and non-protein thiol levels, oxidation of diclorofluorescein. Amphetamine increased the number of crossing and rearing in the open field test and diphenyl diselenide prevented only the increase in the number of crossings when acutely administered to mice. Furthermore, amphetamine increased the time of immobility and stereotypy in mice. Diphenyl diselenide did not prevent these effects. By contrary, at 10 mg/kg, sub-chronic administration of diphenyl diselenide increased per se the time of immobility and stereotypy. It was also found a positive correlation between immobility and stereotypy in acute and sub-chronic treatment with diphenyl diselenide. It was also detected a decrease in brain MAO-B activity caused by sub-chronic treatment with diphenyl diselenide either alone or in combination of amphetamine. Any change was detected in oxidative stress parameters. In conclusion, sub-chronic administration of diphenyl diselenide can promote a behavioral sensitization that seems to be, at least in part, dependent of MAO-B inhibition.